A STUDY OF COST VARIATION ANALYSIS OF ORAL HYPOGLYCEMIC DRUGS AVAILABLE IN INDIAN PHARMACEUTICAL MARKET - Joy, Florance; JL, Marko; Nand, Stephen (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: A large number of oral hypoglycemic drugs as single or fixed dose combinations are available for the treatment of diabetes mellitus which has a wide range of price variation and becomes a constraint in the treatment for both physician and patient. However, very few studies have been done to reveal such price variations. The objective of this study was to find out the cost variation among the different brands of various classes of oral hypoglycemic drugs in similar strength and dosage forms of single therapy and fixed-dose combinations. Methods: Cost of a particular drug being manufactured by different companies in the same strength, number, and dosage form was compared from the Current Index of Medical Specialties (CIMS) (January 2022–April 2022) and Indian Drug review 2022. The difference in the maximum and minimum price of the same drug manufactured by different pharmaceutical companies and the percentage variation in price was calculated. Results: Among single drug therapy, Glimepiride (1 mg) shows a maximum percentage variation in price of 3450%. Among Sulfonylureas-glimepiride (1 mg) shows a maximum price variation of 3450%, in Biguanides–metformin (500 mg), in Thiazolidinediones – Pioglitazone (15 mg) shows a maximum price variation of 900%, and 300%, respectively, and among the glucosidase inhibitors, Voglibose (0.3 mg) shows maximum price variation of 571.2%. Among combination formulation, glimepiride (1 mg) + metformin SR (500 mg) shows a maximum percentage of price variation of 262.1%. Conclusion: It is observed from our results that there is a wide variation in prices of drugs manufactured by different pharmaceutical companies. Hence, it is very necessary for regulatory authorities to regulate the wide variation in drug prices to maximize the benefits of the treatment. It is recommended that the appraisal and management of marketing drugs should be well-regulated.